PENGARUH STRATEGI PEMBELAJARAN PROBING PROMPTING TERHADAP HASIL BELAJAR IPA POKOK BAHASAN SEL PESERTA DIDIK KELAS VII SMP NEGERI 3 SUNGGUMINASA KAB. GOWA - Reni Asmarani Mansyur; Salahuddin .; Wahyuni Ismail (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to (1) know the learning outcomes of science subject of cell learners using learning strategy Probing Prompting class VII students SMPN 3 Sungguminasa Kab. Gowa, (2) to know the learning result of science subject of student cell without using learning strategy of Probing Prompting of class VII SMPN 3 Sungguminasa Kab. Gowa, (3) to know whether there is influence of learning strategy of Probing Prompting to learning result of IPA of cell subject of student class VII SMPN 3 Sungguminasa Kab. Gowa.This research is Quasi Experimental research with Pretest-Posttest Control Group Design research. The population in this study is all students of class VII SMPN 3 Sungguminasa consisting of 11 classes with the number of students as many as 353 people. The sampling technique used is simple random sampling technique. The sample in this study is class VII J which amounted to 32 students and class VII K which amounted 32 students. Instruments used to determine the larning outcomes of learners in the form of multiple choice test as many as 20 numbers. Data analysis techniques used are descriptive statistical analysis and inferential statistical analysis with t-test.The results obtained in both groups through descriptive statistical analysis, the average learning outcomes of learners using learning strategy Probing Prompting of = 80,53 whereas the average learning outcomes of group learners without using the strategy of learning Probing Prompting of = 77,06. The result of inferential analysis of data shows that the significance value obtained tcal 4,663 > ttable 1,671 and significance (0,000 < 0,05). So it can be concluded that there is a positive influence of the use of learning strategy Probing Prompting on learning outcomes IPA subject of cell learners class VII SMP Negeri 3 Sungguminasa Kab. Gowa.